Luminescence properties of Eu(3+)- and Mg(2+)-doped LiTaO(3) obtained via the polymeric precursor method - Gasparotto, G. [UNESP]; Lima, S. A. M. [UNESP]; Davolos, Marian Rosaly [UNESP]; Varela, José Arana [UNESP]; Longo, Elson [UNESP]; Zaghete, M. A. [UNESP] (Elsevier B.V., 2008)
This work reports the pure lithium tantalate (LiTaO(3)), europium (III)-doped LiTaO(3) and magnesium (II)-europium (III)-doped LiTaO(3) preparation by the polymeric precursor method, using four different powered samples of Eu(3+) ion concentrations 0.1 and 1 at%, observing their effect on the luminescent property of the material. Results indicated LiTaO(3) phase free of secondary phases at 650 degrees C and the photoluminescence (PL) emission spectra showed the characteristic sharp emission bands given by Eu(3+) ions when they are excited at a wavelength of 399 rim. An increase of dopants led its to a non-homogeneous broadening and showed a slightly larger one when Mg was added. A displacement of the transition (5)D(0) --> (7)F(0) to shorter wavelengths as function of Eu(3+) concentration was also noticed. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: ferroelectrics; photoluminescence; rare earth